Abrupt Rise of the Longitudinal Recoil Ion Momentum Distribution for Ionizing Collisions - Weber, Th. (2001)
We report on the experimental observation of an abrupt rise in the longitudinal momentum distribution of recoil ions created in proton helium collision. The details of this structure can be related to electrons traveling with the velocity of the projectile [electron capture to the continuum (ECC)]. The longitudinal as well as the transverse distribution of the recoil ions can be explained as a continuation of the momentum distribution from ions resulting from electron capture illustrating the smooth transition from the capture to bound states of the projectile to the ECC.